Robert Louis Stevenson - his life and works - Thompson, Dora (My University, 1895)
Introduction: When we see a man who is fired by genius, full of bright thoughts and with a clear and faultless style of expressing them. A man who not only writes of men but is a man himself—and who when we read him makes us to wonder if such perfect expression can come from mortal men: where, I say, we see such an one succumb to disease in the prime of his manhood and in the harvest time of his genius. After he is taken from us we realize how great has been our loss—and wonder if after all he was not some spirit who was here but for a little time to brighten up this prosy old world of ours by telling us of the customs and manners of a different people. Such a man was Robt. Louis Stevenson and with his death on the third of last December Scotland lost another of her list of famous writers and the world one of its most valuable contributors to its storehouse of knowledge and romance. He was one of the few writers whose personality reached through his books to his readers and it is through them that we get at the real life and character of the man. His stories tell us of physical intellectual and moral fight. The idea of conflict always interested him—he thus reveals his own character and life which was a continual struggle with disease.
Citation: Thompson, Dora. Robert Louis Stevenson - his life and works. Senior thesis, Kansas State Agricultural College, 1895.
Morse Department of Special Collections
Keywords: English; Robert Lewis Stevenson; Literature; Theses; Manuscripts (documents)